AB1213 Anti TNF dosage reduction response in juvenile idiopathic arthritis associated to enthesitis patients who achieved clinical remission. (23rd January 2014) - Torrente-Segarra, V.; Juanola, X.; Bou, R.; Ricart, S.; Antόn, J.; Nolla, J.M.
Abstract : Background: Juvenile Idiopathic Arthritis (JIA) related to Enthesitis (JIA-ERA) it means 10-15% of all JIA patients. Once NSAID, methotrexate and corticosteroids fail to control disease activity, the use of an anti-TNF alpha is recommended. Once clinical remission is reached, the amount of time recommended to mantain the anti-TNF is unknown. Objectives: To describe the response to the reduction of anti-TNF dosage in JIA-ERA patients who achieved clinical remission with medication. Methods: We describe 4 cases of JIA-ERA who received anti-TNF treatment and reached clinical remission. After, at least, 12 months of clinical remission, anti-TNF dosage was tappered by increasing the week interval of anti-TNF administration (50mg every 2 weeks in etanercept; 40mg every 4 weeks in adalimumab). We considered clinical remission with medication (Wallace criteria) those patients who had inactive disease for 6 months: no arthritis, no enthesitis, no inflammatory low back pain, normal CPR and ESR, and VAS Physician=0). We collected following data: clinical features, age of onset, clinical features, B27 presence, acute phase reactants at onset, initial treatment, first DMARD, anti-TNF, remission time prior to dosage reduction, total time in remission with tappered dosage. We tappered anti-TNF treatment to those patients who stayed at least 12 months in clinical remission. Results: The table shows patients' features. Conclusions: The reduction of anti-TNF dosage seems a right decision in JIA-ERA patients who reached clinical remission. This condition implies a reduction in JIA-ERA treatment costs, maintaining same effectivity and higher efficiency. Disclosure of Interest: None Declared